Nurses at the frontline of public health emergency preparedness and response: lessons learned from the HIV/AIDS pandemic and emerging infectious disease outbreaks. Issue 10 (October 2021) - Guilamo-Ramos, Vincent; Thimm-Kaiser, Marco; Benzekri, Adam; Hidalgo, Andrew; Lanier, Yzette; Tlou, Sheila; de Lourdes Rosas López, María; Soletti, Asha B; Hagan, Holly
Summary: The years 2020–21, designated by WHO as the International Year of the Nurse and Midwife, are characterised by unprecedented global efforts to contain and mitigate the COVID-19 pandemic. Lessons learned from successful pandemic response efforts in the past and present have implications for future efforts to leverage the global health-care workforce in response to outbreaks of emerging infectious diseases such as COVID-19. Given its scale, reach, and effectiveness, the response to the HIV/AIDS pandemic provides one such valuable example, particularly with respect to the pivotal, although largely overlooked, contributions of nurses and midwives. This Personal View argues that impressive achievements in the global fight against HIV/AIDS would not have been attained without the contributions of nurses. We discuss how these contributions uniquely position nurses to improve the scale, reach, and effectiveness of response efforts to emerging infectious diseases with pandemic potential; provide examples from the responses to COVID-19, Zika virus disease, and Ebola virus disease; and discuss implications for current and future efforts to strengthen pandemic preparedness and response.